1999
DOI: 10.1111/1467-9566.00147
|View full text |Cite
|
Sign up to set email alerts
|

Medicines and the maintenance of ordinariness in the household management of childhood asthma

Abstract: This paper applies and extends the 'adaption' perspective on chronic illness by arguing that, in the case of moderate childhood asthma, an important aspect of the process may be found in the ways in which children and parents construct a sense of their ordinariness. It is suggested that medicines may play a role in this process. Reporting an intensive and detailed qualitative study of the management strategies of nine English families, it is shown that household members did not generally regard asthma as a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 5 publications
(6 reference statements)
6
83
1
Order By: Relevance
“…(PP) 162/165 Asthma medicines seen as preferable to avoidance/(non-medical) preventive strategies 162/165 But because asthma medicines seen as so effective, hospital admission delayed even when serious 162 So possibly inhaler/reliever medicines over used, but preventer medicines underused (PP) 162/165 Purposeful adherence (or possibly non-purposeful adherence -not adherence) Acceptors…”
Section: Benefits Of Asthma Medicationmentioning
confidence: 99%
See 3 more Smart Citations
“…(PP) 162/165 Asthma medicines seen as preferable to avoidance/(non-medical) preventive strategies 162/165 But because asthma medicines seen as so effective, hospital admission delayed even when serious 162 So possibly inhaler/reliever medicines over used, but preventer medicines underused (PP) 162/165 Purposeful adherence (or possibly non-purposeful adherence -not adherence) Acceptors…”
Section: Benefits Of Asthma Medicationmentioning
confidence: 99%
“…Rather, she suggested that reliance on medicine as a response to ill health can be regarded as culturally rooted. Prout et al 162 investigated the role of medicine in the lives of families with asthma and concluded that people much prefer it to the 'non-medical' preventive strategies that are advocated alongside the use of inhalers.…”
Section: Sociological and Anthropological Studies Challenging Compliancementioning
confidence: 99%
See 2 more Smart Citations
“…For example Prout et al (1999) wrote about the ways in which inhalers were used in a family to maintain 'ordinariness' for children with asthma, while Willems (2000) explored their use as a technology of self care. In SHI, debate has recently returned to the meaning and use of medicine, putting space back in more explicitly.…”
Section: Materialities Of Home Health: Attending To Technology and Placementioning
confidence: 99%